Pendidikan Islam: Peluang dan Tantangan di Era Global dan Multikultural - Agus Samsul Bassar; Uus Ruswandi; Mohamad Erihadiana (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Humans are living currently in a global and multicultural era made easy with the advancement of Science and Technology, especially Digital Technology that affects lifestyles and human behavior in all aspects of life. Islamic education plays a strategic role in preparing good people who are always serving Allah and benefiting others, especially in preparing a righteous people whocan surf in complexity, chaos, and turbulences. In this study, the authors research how the opportunities and challenges of Islamic Education in the global and multicultural era in preparing a righteous people who can surf in the global and multicultural era. This research with a qualitative approach, use a type of Library Research with descriptive methods. The results of the research show that Islamic Education has strategic opportunities to contribute and give solutions, especially for millennials to increase their faith, by enhancing the understanding, appreciation and human experience in practicing Islam. With the hope of helping them to become Muslim who have a strong faith and devotion to Allah SWT and have a noble character in their personal lives, society, nation, and state in the global and multicultural era. The challenges of Islamic Education demanded to adjust to the progress of the 21st century learning trends and Muslim educators have the necessary skills for the 21st Century. Including Islamic educational institutions need to hold a variety of innovations and creations in the face of a time that is changing rapidly and full of uncertainty, to continue to exist and be able to provide excellent service for the peoples.